Efektivitas Taktik Mengajar Punggung Dengan Punggung Terhadap Hasil Belajar Biologi Siswa Pada Materi Sistem Reproduksi Di Kelas X - Lauren, Ivan; Crysty, Verronicha (Jurnal Pendidikan Indonesia, 2022)
This study aims to determine the influence of the use of Back with Back teaching tactics on student biology learning outcomes on reproductive system material in class X of SMK Kesehatan Imelda Medan for the 2018/2019 Learning Year. This research is a type of experimental research. The population in this study consisted of 4 classes and the sample was 2 classes. Results on the test data obtained an average of 76.59 for the learning outcomes of students taught using back-to-back teaching strategies, compared to an average of 68.12 for traditional learning. From the results of the hypothesis test, the > t table was obtained, namely 4.57 > 2.372 and the significance level of α=0.01, namely Ha was accepted which showed that both had a significant effect on students. biology learning outcomes Back and back classes and routine types